2022
DOI: 10.1007/s13167-022-00272-7
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic phenotyping of tear fluid as a prognostic tool for personalised medicine exemplified by T2DM patients

Abstract: Background/aims Concerning healthcare approaches, a paradigm change from reactive medicine to predictive approaches, targeted prevention, and personalisation of medical services is highly desirable. This raises demand for biomarker signatures that support the prediction and diagnosis of diseases, as well as monitoring strategies regarding therapeutic efficacy and supporting individualised treatments. New methodological developments should preferably rely on non-invasively sampled biofluids like s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…(3) Currently, Metabo-tip stands out as the only technique capable of shortinterval metabolic biomonitoring/phenotyping in humans. (3) Such methods at hand mean that the biomedical challenge associated with chronic diseases boils down to mathematical problems. Methods for metabolic biomonitoring deliver a large number of data points, which depend on physiological activities affected by multiple factors related to your state of health, lifestyle parameters (eating, smoking, physical exercise) or pharmacological therapy.…”
Section: Applying Artificial Intelligence: What Is Metabo-tip?mentioning
confidence: 99%
“…(3) Currently, Metabo-tip stands out as the only technique capable of shortinterval metabolic biomonitoring/phenotyping in humans. (3) Such methods at hand mean that the biomedical challenge associated with chronic diseases boils down to mathematical problems. Methods for metabolic biomonitoring deliver a large number of data points, which depend on physiological activities affected by multiple factors related to your state of health, lifestyle parameters (eating, smoking, physical exercise) or pharmacological therapy.…”
Section: Applying Artificial Intelligence: What Is Metabo-tip?mentioning
confidence: 99%
“…Glucose and lactate are two well-established tear analytes [ 75 , 76 , 77 , 78 , 79 ]. In addition, tear fluid is a rich source for metabolic phenotyping [ 80 ]. Tears of diabetic patients show elevated levels of several metabolites, such as carnitine, tyrosine, uric acid, and valine [ 80 ].…”
Section: Non-invasively Accessible Resources For Biomarkersmentioning
confidence: 99%
“…In addition, tear fluid is a rich source for metabolic phenotyping [ 80 ]. Tears of diabetic patients show elevated levels of several metabolites, such as carnitine, tyrosine, uric acid, and valine [ 80 ]. Increased levels of inflammatory cytokines and chemokines in tears, including IL-6, IL-1, IL-8, IL-10, and TMF-α, have been investigated in patients with dry eye disease.…”
Section: Non-invasively Accessible Resources For Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of innovative screening method contributes to promote population health by health risk assessment, individualized, and cost-effective profiling. It has been highlighted that homocysteine (Hcy)/uric acid (UA) metabolism and cardiovascular diseases are several areas considered to be potentially strongly benefiting from the PPPM/3PM paradigm [ 11 , 12 ]. Koklesova et al reported that the metabolic pathway of Hcy is closely related to coronary artery disease and atherosclerosis, which is of great value for disease diagnosis and prediction, and helps to optimize the individualized comprehensive treatment of patients [ 11 ].…”
Section: Introductionmentioning
confidence: 99%